2008
DOI: 10.1111/j.1601-0825.2008.01449.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of chlorhexidine in the maintenance of oral candidiasis‐free period in HIV infection

Abstract: OBJECTIVE-To determine if chlorhexidine can be used as an intervention to prolong the time to relapse of oral candidiasis.SUBJECTS AND METHODS-A double-blinded randomized clinical trial was performed in 75 HIV/AIDS subjects with oral candidiasis. Clotrimazole troche was prescribed, and the subjects were re-examined every 2 weeks until the lesions were completely eradicated. The subjects were then randomly divided into two groups; 0.12% chlorhexidine (n = 37, aged 22-52 years, mean 34 years) and 0.9% normal sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…A study of 0.12% chlorhexidine mouthrinse showed a small, but not statistically significant, effect in maintenance of an OC-free period in HIV-infected adults in one double-blind randomized clinical trial. 28 A pilot study in children with HIV suggested that daily topical disinfection with chlorhexidine has potential for reduction in candidal colonization and subsequent infection with OC. 29 The use of a 0.025% lawsone methyl ether mouthwash in a small comparison trial to 0.2% chlorhexidine mouthwash for 2 weeks in HIV-infected and denture-wearing patients in Thailand demonstrated comparable lack of development of drug resistance and no significant changes in genotype.…”
Section: Resultsmentioning
confidence: 99%
“…A study of 0.12% chlorhexidine mouthrinse showed a small, but not statistically significant, effect in maintenance of an OC-free period in HIV-infected adults in one double-blind randomized clinical trial. 28 A pilot study in children with HIV suggested that daily topical disinfection with chlorhexidine has potential for reduction in candidal colonization and subsequent infection with OC. 29 The use of a 0.025% lawsone methyl ether mouthwash in a small comparison trial to 0.2% chlorhexidine mouthwash for 2 weeks in HIV-infected and denture-wearing patients in Thailand demonstrated comparable lack of development of drug resistance and no significant changes in genotype.…”
Section: Resultsmentioning
confidence: 99%
“…OC in HIV-infected children and adults can be treated and relapses prevented by applying disinfecting mouth rinses containing chlorhexidine 0.12 % 1–2× daily for a 90-day period [127, 128]. In the pre-HAART era, secondary prophylaxis or life-long therapy with fluconazole led to significant reductions of chronic recurring oropharyngeal candidiasis—but it has also led to the development of secondary resistance [129, 130].…”
Section: Results/guidelinesmentioning
confidence: 99%
“…failed to observe reductions in yeast prevalence following 0.12% chlorhexidine mouthrinse use and provision of oral hygiene instructions. In a RCT, 35 Nittayananta et al. observed a small but insignificant delay in time to relapse of candidiasis in HIV‐positive patients (previously cured of candidiasis with clotrimazole) using a 0.12% chlorhexidine mouthrinse as opposed to a 0.9% saline mouthrinse.…”
Section: Resultsmentioning
confidence: 99%